Prevalence of Food Insecurity among Women in Rural Area of North West Bangladesh - Rahman, Azizur; Karim, Rezaul (Pakistan Journal of Nutrition, 2013)
Food insecurity is a public health concern among rural poor in Bangladesh. Food insecurity is the insufficiency of good quality foods, reduced access to foods and inadequate intake of foods to meet ones physiological demands. Food insecurity is inversely associated with health and nutritional status of rural women of Bangladesh. This cross-sectional study was conducted using an interview-based pre tested questionnaire. Data were collected from 500 women in low-income areas of Nageswari and Phulbari sub district of Kurigram district of Bangladesh; from February to October 2012. Both of them have border with India. From each of the sub district 250 women were selected for the interview. Food insecurity was assessed using the short form of the United States food security survey module. The prevalence of food insecurity was 32.4%. The socioeconomic factors that increase the risk of food insecurity are-income below the poverty line, illiteracy, women heading the household, unemployment and lack of own housing. No association was found between obesity and food insecurity. The food-insecure women with hunger had lower intake of all food-groups expect grains. This study determines that the food insecurity is present in the rural area of North West Bangladesh. Food-insecure women with hunger are at a risk of malnutrition. Interventions that target reduction of the factors associated with food insecurity are necessary in the rural food insecure area of Bangladesh.